Production scheduling in no-wait flow shop system minimizing total flow time - Scardoelli, Lucas Yamada; Nagano, Marcelo Seido; Moccellin, João Vitor (Revista Gestão da Produção Operações e Sistemas, 2008)
This paper deals with the no-wait flow shop scheduling problem with the objective of minimizing total flow time,therefore reducing in-process inventory. Two news heuristic methods are proposed for the scheduling problemsolution. The performance of the news methods are evaluated and compared with the best heuristic reported inthe literature. Experimental results show the new methods superiority for the test problems set.Keywords: in-process inventory, no-wait flow shop, heuristics methods.